2019
DOI: 10.1200/jco.2019.37.15_suppl.6635
|View full text |Cite
|
Sign up to set email alerts
|

The effect of guideline-concordant novel therapy use on meeting cost targets in OCM: Results from a large community oncology network.

Abstract: 6635 Background: The Oncology Care Model (OCM) is intended to incentivize physicians to improve the quality and reduce the cost of cancer care. In OCM, providers are accountable for all costs during six month episodes of care relative to target costs (TC) derived from a baseline spending period (BSP; 2013-2015). This accountability is intended to foster care coordination to reduce preventable emergency department visits and hospitalizations (EDH). Benefits of reducing EDH may be diluted when new treatment ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“… 6 The current study used more rigid cohort definitions in identifying patients potentially eligible to receive novel therapies, but because of the smaller sample size, all chemotherapy and immunotherapy novel treatments were combined in 1 analysis, and no statistically significant differences were found in the receipt of novel therapies before and after implementation of the OCM. Despite the concerns raised specifically regarding patients with lung cancer treated with immunotherapy, 8 this study found an increase in receipt of novel immunotherapy after the start of the OCM for patients treated by participating clinicians, echoing findings from Keating et al 6 In combination, the results of these 2 studies may reassure patients, clinicians, and policy makers that the OCM does not appear to discourage the use of novel therapies despite incentives to reduce cancer spending.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“… 6 The current study used more rigid cohort definitions in identifying patients potentially eligible to receive novel therapies, but because of the smaller sample size, all chemotherapy and immunotherapy novel treatments were combined in 1 analysis, and no statistically significant differences were found in the receipt of novel therapies before and after implementation of the OCM. Despite the concerns raised specifically regarding patients with lung cancer treated with immunotherapy, 8 this study found an increase in receipt of novel immunotherapy after the start of the OCM for patients treated by participating clinicians, echoing findings from Keating et al 6 In combination, the results of these 2 studies may reassure patients, clinicians, and policy makers that the OCM does not appear to discourage the use of novel therapies despite incentives to reduce cancer spending.…”
Section: Discussionsupporting
confidence: 63%
“…Some single-practice reports suggested that patients who receive standard of care treatment with novel therapies, including patients with lung cancer treated with immunotherapy, had health care spending that exceeded OCM-defined cost thresholds and could theoretically alter physician prescribing of novel therapies. 8 , 9 However, another study that used broader cohort definitions and ascertained eligibility for novel therapies based solely on diagnosis with a cancer for which a novel therapy is approved found either no association (for chemotherapy for 5 cancers and immunotherapy for 1 cancer) or an association with limited cancer types (for immunotherapy for 2 cancers). 6 The current study used more rigid cohort definitions in identifying patients potentially eligible to receive novel therapies, but because of the smaller sample size, all chemotherapy and immunotherapy novel treatments were combined in 1 analysis, and no statistically significant differences were found in the receipt of novel therapies before and after implementation of the OCM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A cross-sectional analysis by Parikh et al 16 found that oncologists participating in the OCM varied in their demographic characteristics, care intensity, and exposure to alternative models compared with nonparticipating oncologists in ways that practice-level analyses might meaningfully miss, motivating physician-level analysis. While there is some early suggestive evidence that the OCM altered hospitalization rates 17 and other descriptive or non-peer-reviewed work, 16,[18][19][20][21][22][23][24][25][26][27] there remain few assessments of the OCM's potential effects on care choices. 14 This study evaluates whether OCM participation was associated with clinician behavior within the context of their practices.…”
Section: Introductionmentioning
confidence: 99%